Analisis Peranan Income Audit Pada Pengendalian Internal Di Hotel The Westin Resort & Spa Ubud Bali - Pande Made Karina Bimantari; I Putu Arnawa; I Gusti Ngurah Agung Wiryanata (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the role of income audit in the implementation of internal control at The Westin Resort & Spa Ubud Bali Hotel, specifically in auditing revenues originating from the Food & Beverage department. Income audit is an important process that functions to ensure the accuracy and reliability of daily revenue reports, as well as prevent errors or fraud that can be detrimental to hotel management. This study uses a qualitative descriptive method, with data collection techniques through in-depth interviews with related parties, direct observation of work processes, and documentation of reports and procedures used in the revenue audit process. Data analysis was carried out using the internal control framework according to the Committee of Sponsoring Organizations of the Treadway Commission (COSO) which includes five components, namely: (1) control environment, (2) risk assessment, (3) control activities, (4) information and communication, and (5) monitoring. The results of the study indicate that income audit has a significant role in supervising, verifying, and ensuring that all revenue transactions are recorded correctly based on valid transaction evidence. Income audit also helps detect discrepancies or potential fraud in revenue reporting, thus contributing directly to the effectiveness of internal control. However, several challenges were identified in its implementation, such as a lack of understanding of procedures by some employees and suboptimal coordination between relevant departments. Therefore, improving cross-departmental training and communication is crucial to support the overall effectiveness of the internal control system. This research is expected to provide practical contributions to hotel management in improving revenue audit systems and strengthening internal controls in the competitive and dynamic hospitality industry.